Effect of Managers' Communication on Training Application with Motivation to Learn as an Intervening Variable - Ismail, Azman; Foboy, Nurul Afiqah; Nor, Azmawaty Mohamad (UI Scholars Hub, 2018)
Research Aims - According to the present research concerning organizational training, managers’ communication are often seen as a critical training management issue that may help to maintain and enhance organizational competitiveness and performance in a borderless world and era of globalization. In this study, the relationship between managers’ communication, motivation to learn and training application was evaluated at military hospitals in Peninsular Malaysia. Design/methodology/approach - The SmartPLS path model analysis was utilized to examine the research hypotheses and evaluate the validity and reliability of instrument used. Research Findings - The results demonstrate that the capability of managers to communicate the training courses information will strongly invoke employees’ motivation to learn. Theoretical Contribution/Originality - As a result, this motivation may lead to an improved training application in a military health context. Managerial Implication in the South East Asian context - Managers play a critical role in dissemination of the organisation’s aspiration to the rank and file. Research limitation & Implications - The conclusion of this study should be taken carefully with some methodological and conceptual limitations.